2002
DOI: 10.1557/proc-745-n7.6/t5.6
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy defects in tantalum pentoxide: a density functional study

Abstract: First principles total energy calculations were performed in order to characterize O vacancy defects in Ta2O5. A simplified version of the crystalline orthorhombic phase of Ta2O5 was used in this study. Results indicate that O vacancies in Ta2O5 can be broadly classified based on their location in the lattice. One type of vacancies (occupying the “in-plane” sites) displays deep or mid gap occupied states, and shallow unoccupied states, while a second type (occupying “cap” sites) results in shallow occupied sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Ta− O bond lengths were within the range of 1.899−2.139 Å with an average value of 1.988 Å and thus in good agreement with reported experimental results. 68 The calculation results also suggested that Ta 16 O 40 has electronic properties similar to those of bulk Ta 2 O 5 . Figure 4a shows the highest occupied molecular orbital (HOMO) and LUMO of Ta 16 O 40 , which are derived from the O 2p and Ta 5d orbitals, respectively.…”
Section: Experimental and Computational Detailsmentioning
confidence: 68%
“…The Ta− O bond lengths were within the range of 1.899−2.139 Å with an average value of 1.988 Å and thus in good agreement with reported experimental results. 68 The calculation results also suggested that Ta 16 O 40 has electronic properties similar to those of bulk Ta 2 O 5 . Figure 4a shows the highest occupied molecular orbital (HOMO) and LUMO of Ta 16 O 40 , which are derived from the O 2p and Ta 5d orbitals, respectively.…”
Section: Experimental and Computational Detailsmentioning
confidence: 68%